Pengaruh Model Two Stay Two Stray Terhadap Hasil Belajar Bahasa Indonesia Kelas V SDN Gugus XI - Gufita, Nurma; Yuliantini, Nani; Dalifa (Universitas Bengkulu, 2025)
The objective of this research is to explore how the cooperative learning approach known as